Coal Upgrading: Desulfurization and Dehydration of Low-Rank Coal and High-Rank Coal through Blending Method - Sardi, Bambang; Nurhidayat; Safitri, Nina (Tadulako Science and Technology Journal, 2020)
Introduction : Sulawesi coals contain significantly high of sulfur. This makes it not suitable to be used as fuel, unless it went through an engineering process so that the use of low-rank coals can be optimized by preserving the environmental impacts that may be caused. The process is in the form of upgrading the coals through physical desulfurization and dehydration with blending method. The purpose is to make coal meet the fuel use standard in industry. This study used low-rank coal from Pattuku (BP),while the high-rank coal studied was from PT Semen Tonasa (BT) on a dry base with a size of 100 mesh. The variables observed were the smallest total sulfur content, the largest calorific value, and the smallest (optimal) water content. The results showed that the total sulfur content in all variations of BT:BP ratios are 1:0, 3:1, 1:1, 1:3 and 0:1. Thus, based on the ratios, the coal fulfilled the standard to be used as fuel for cement industry while the variation of BB that fulfilled the standard to be used as coal-fired power plants had ratios of 1:0, 3:1 and 1:1. The smallest (optimal) total sulfur level was 0.1046% at the BB ratio of 1:0. BB water content in all variations of BT: BP ratiosmetthe standard to make it as fuel for cement industry and coal-fired power plant (PLTU). The smallest (optimal) water content was 2.48% on the blending coal ratio of 0:1. The calorific values of BB on all variations of BT:BP met the standard to be used as fuel for cement industry had ratios of 3:1, 1:1 and 1:3,yet there was no single BB that metthe standard to be used as coal-fired power plant (PLTU). The largest (optimal) calorific value was 6.506.39 kcal/kg at the BB ratio of 0:1.